Possibilities of using soil microarthropods, with emphasis on mites (Arachnida, Acari, Mesostigmata), in assessment of successional stages in a reclaimed coal mine dump (Pszów, S Poland) - MADEJ, GRAŻYNA; KOZUB, MONIKA (Biological Letters, 2015)
The usefulness of 2 methods for biomonitoring of the effects of land rehabilitation were compared in Pszów (Upper Silesian Coal Basin, south of Poland). Thirty-one species of mesostigmatid mites were collected from 3 study plots representing different stages of restoration of the mine dump Wrzosy in Pszów and community structure of the mites was analysed. There was a general trend for mesostigmatid species richness, diversity, and density to increase with the development of vegetation. The dominant early successional mesostigmatid species was the phoretic Hypoapis claviger. During this study, 4616 specimens of soil microarthropods were extracted in total. They were classified according to the Biological Soil Quality Index (QBS). We tested the sensitivity and usefulness of this index for monitoring of soil quality and found its good relationship with successional stages in the reclaimed mine dump. Thus the QBS index seems to be an efficient index for monitoring the effects of restoration in mine dumps. It is a simpler, quicker, and cheaper bioindicator method than the earlier method based on community structure analysis of mesostigmatid mites.